2019
DOI: 10.1177/0145561319846460
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitrous Oxide on the Outcomes of Underlay Tympanoplasty: A Prospective Study

Abstract: The main aims of tympanoplasty are eradication of chronic middle ear disease, repair of the tympanic membrane, and restoration of hearing. Nitrous oxide (N2O) is not a commonly preferred anesthetic agent for tympanoplasty because this agent may increase middle ear pressure and displace the graft. In this study, we researched the surgical outcomes of the underlay tympanoplasty performed with N2O anesthesia. Patients who underwent tympanoplasty were included in this prospective study. A type 1 tympanoplasty was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Receiving nitrous oxide anesthesia did not significantly impact anatomic or hearing outcomes. 62 The univariate analysis conducted by Albu et al 13 showed that having a healthy opposite ear, a long dry period leading up to operation, and nonsmoking status all significantly predicted anatomic success. Their multivariate analysis confirmed that the dry period was a significant predictor of success.…”
Section: Suppurative Otitis Mediamentioning
confidence: 99%
“…Receiving nitrous oxide anesthesia did not significantly impact anatomic or hearing outcomes. 62 The univariate analysis conducted by Albu et al 13 showed that having a healthy opposite ear, a long dry period leading up to operation, and nonsmoking status all significantly predicted anatomic success. Their multivariate analysis confirmed that the dry period was a significant predictor of success.…”
Section: Suppurative Otitis Mediamentioning
confidence: 99%